PENGARUH TERAPI AL-QUR’AN SURAH AL-ANFAL AYAT 72 UNTUK MENINGKATKAN PENGENDALIAN DIRI SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMP TRI BHAKTI PEKANBARU - Ningsih, Ramja; Umari, Putri; Donal, Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of the study is to describe the self-control of students in SMP Tri Bhakti Pekanbaru before and after being given therapy Al-Qur’an surah Al-Anfal verse 72 with guidance group, knowing the differences and influence of the therapy Al-Qur’an surah Al-Anfal verse 72 with guidance group to improve self-control of SMP Tri Bhakti Pekanbaru. The study was conducted at SMP Tri Bhakti Pekanbaru against 8 subjects with a purposive samplin teachnique. The research design was pre-experiment with the one group pre-test post-test model. The instrument of data collection used is the scale of measurement of self-control. The study showes that there were differences in self-control berfore and after the therapy Al-Qur’an surah Al-Anfal verse 72 based on the wilcoxon test results showed a significance value of 0,012 < 0,05. In addition, based on the Spearman rank test it is known that there is a significant influence between therapy Al-Qur’an surah Al-Anfal verse 72 on students' self-control with a significance value of 0,028 < 0,05. The influence of therapy Al-Qur’an surah Al-Anfal verse 72 on students’ self-control is 58% while 42% is influenced by other factors that come from within and from the student's environment.Key Words: Therapy Al-Qur’an, Surah Al-Anfal verse 72, Self-control, Group Guidance